Overexpression of B7-H3 in α-SMA-Positive Fibroblasts Is Associated With Cancer Progression and Survival in Gastric Adenocarcinomas - Zhan, Shenghua; Liu, Zhiju; Zhang, Min; Guo, Tianwei; Quan, Qiuying; Huang, Lili; Guo, Lingchuan; Cao, Lei; Zhang, Xueguang (Frontiers in Oncology, 2020)
Background B7-H3 promotes tumor immune escape and is highly expressed in tumor tissues. Stromal cells in tumors including fibroblasts play an important role in this process; however, the role of B7-H3 in tumor fibroblasts has not been fully clarified. Methods We examined B7-H3, CD31, and alpha-smooth muscle actin (α-SMA) protein expression in 268 gastric adenocarcinomas by immunohistochemistry. The coexpression of B7-H3 with CD31 or α-SMA was examined using immunofluorescence double staining. Cytokine expression from fibroblasts treated with B7-H3 small interfering RNA (siRNA) was analyzed by Quantitative reverse transcription–polymerase chain reaction (qPCR) and Enzyme-linked immunosorbent assay (ELISA). The transwell tests were conducted to assess the migration and invasion ability of fibroblasts. The overall survival was analyzed by Kaplan–Meier analysis. Associations between categorical variables were assessed using the Pearson’s Chi-square test or Fisher’s exact test. Results GAC patients with B7-H3 expression showed a significantly poorer survival (P = 0.012). The overall survival of the group with high B7-H3 expression was significantly worse than the group with low B7-H3 expression in both tumor cells and in stromal cells (P = 0.007, P = 0.048). B7-H3 expression correlated with many clinicopathological data, including tumor stage, tumor depth, lymph node involvement and survival. Immunofluorescence staining showed that B7-H3 was expressed in tumor cells and α-SMA-positive fibroblasts. Remarkably, high expression of α-SMA was associated with a poor prognosis (P = 0.007), and the prognosis of patients with high stromal expression of B7-H3 and α-SMA was significantly worse than that of other combination types (P = 0.001). Additionally, the absence of B7-H3 led to decreased secretion of cytokines such as interleukin (IL)-6 and vascular endothelial growth factor (VEGF) as well as a declined migration and invasion ability in cancer associated fibroblasts (CAFs).